Pengendalian Kualitas Produk Menggunakan Diagram Kontrol Multivariat p - Bayu Iswahyudi Noor; Ika Purnamasari; Fidia Deny Tisna Amijaya (EKSPONENSIAL, 2019)
Every company competes with other companies in similar industries. One way to win the competition or at least stay in the competition is to give full attention to the quality of the products, so it can outperform the products produced by a competitors company. Quality control is done at the stage of production process, in order to get the standard or quality as expected. Multivariate p chart is one of the methods used for quality control which is the development of the control chart p. This research is conducted in the newspaper company Kaltim Post, with the characteristics quality of color blur, not symmetrical and dirty. The research is conducted in two phases; phase I is conducted for the period of July 2017 and phase II is conducted for the period of August 2017. The purpose of this research is to know the result of the controlling production of Kaltim Post newspaper by using multivariate p chart , knowing the types of defects that often occur and the cause of the defects types. The result of controlling production of Kaltim Post newspaper using multivariate diagram p is controlled in phase I with upper control limit of 0.002736, center line of 0.0024224 and lower control limit of 0.0021087. So the limits in phase I are appropriate for use in phase II. The most common types of defects are colors blur the caused by machine, method, material, human, and environmental factors.